Pre-Service Teachers Perception and Strategies in Teaching English as a Lingua Franca in Indonesia - Cahyadi, Ihsan Alfa; Fitriyah, Ulil (Universitas Pendidikan Mandalika, 2024)
English is evolving into a lingua franca, reflecting its capabilities in global communication. Educators are challenged to prepare students for this linguistic landscape. The ELF teaching component facilitates effective cross-cultural communication, Â which is essential in today's interconnected world. This study aims to explore the implementation and pre-service teachers' perceptions of English as a Lingua Franca (ELF) and provide insights for Indonesian teacher preparation programs and curriculum development. The research design used mixed methods, with questionnaires and interviews as research instruments, and involved 64 pre-service English teachers in Indonesia. Convenience sampling was used to collect quantitative data. Google Form responses from the participants were taken for data analysis and tabulation. Descriptive statistics were conducted on the data using the Statistical Package for the Social Sciences (SPSS v. 20). The results show the importance of improving pre-service teachers' understanding and implementation of ELF teaching practices in Indonesia. They need assistance in implementing ELF-based teaching approaches. Recommendations are given to incorporate ELF more effectively into the curriculum and teacher training to support the development of their teaching skills. Therefore, ELF teaching not only influences English language teaching but also plays an essential role in preparing students to communicate in a multilingual global context. Through better understanding and implementation of ELF teaching practices, teachers can help students develop critical cross-cultural communication skills.